PENGARUH DIGITAL MARKETING TERHADAP CUSTOMER ENGAGEMENT DAN KINERJA PEMASARAN UMKM DI KOTA KENDARI - Dzulfikri Azis Muthalib (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine the influence of digital marketing on customer engagement and marketing performance of Micro, Small, and Medium Enterprises (MSMEs) in Kendari City, Southeast Sulawesi. The research employs a quantitative explanatory approach with a sample of 110 MSME owners and managers selected through purposive sampling. Data were collected using structured questionnaires measuring digital marketing dimensions (social media marketing, content marketing, email marketing, search engine optimization, and online advertising), customer engagement (cognitive, emotional, and behavioral), and marketing performance (sales growth, customer acquisition, brand awareness, and customer retention). Data analysis utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test direct and indirect relationships. Results indicate that digital marketing has a significant positive effect on customer engagement and marketing performance. Customer engagement also significantly mediates the relationship between digital marketing and marketing performance. These findings provide theoretical contributions to digital marketing literature in the MSME context and practical implications for MSME owners in optimizing digital strategies to enhance engagement and business performance.